O jogo pela democratização do planejamento na cidade e os caminhos da participação popular no plano diretor de Fortaleza (2002-2008) - Paiva, Antonio Gilvan Silva (2008)
This dissertation examines the experience of popular participation in the revision of the Fortaleza Master Plan between 2002 and 2008. The research aims to verify to what extent this has contributed to the democratization of city planning and to the emer gence of new action strategies of social movements, with a view to guaranteeing, in the approved text, the instruments of the City Statute. The methodology used was ba sed on obtaining primary and secondary data, bibliography on urban issues and the presence of the author in several meetings, Forums and Congresses, which allowed the process to be observed in a comprehensive and dialectical manner. The author concludes that the participation process, despite its peculiar characteristics, which took place in two phases, contributed to a greater democratization of urban planning, al though there were many contradictions and limitations to its implementation.